2010
DOI: 10.1021/jp1030575
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Oxidation at the Ni/Yttria-Stabilized Zirconia Interface: A Study Based on Density Functional Theory

Abstract: A new mechanism for hydrogen oxidation on the nickel/yttria-stabilized zirconia (Ni/YSZ) interface is proposed based on density functional theory. The new mechanism involves oxidation of hydrogen by the oxygen atoms that are bound to both nickel and zirconium (or yttrium) at the interface. The free energy change (∆G) for this pathway is compared to ∆G for reaction steps of previously proposed oxidation mechanisms involving spillover of oxygen from YSZ to nickel or hydrogen spillover from nickel to YSZ. For all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
94
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(110 citation statements)
references
References 30 publications
15
94
1
Order By: Relevance
“…YSZ is a key component of the SOFC anode where it forms an interface with a catalytic metal and a gas phase. The interface region is referred to as the anode triple phase boundary (TPB) [3][4][5][6][7][8] . There is a growing interest in developing predictive models of the physical and chemical properties of YSZ and its surfaces in order to model the chemistry occurring at the anode TPB.…”
Section: Introductionmentioning
confidence: 99%
“…YSZ is a key component of the SOFC anode where it forms an interface with a catalytic metal and a gas phase. The interface region is referred to as the anode triple phase boundary (TPB) [3][4][5][6][7][8] . There is a growing interest in developing predictive models of the physical and chemical properties of YSZ and its surfaces in order to model the chemistry occurring at the anode TPB.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the papers are discussed on the dissociation of H 2 O to OH and H [10][11][12][13]16,22], as a one of the steps of steam reforming reaction on Ni surface. Limited papers are reported about the oxidation reaction on Ni surface assuming the SOFC anode [21,[31][32][33][34][35]. However, the chemical reaction analysis on the clean Ni surface is main target in the previous papers.…”
Section: Introductionmentioning
confidence: 99%
“…So we select the Ni/YSZ þ O system with an extra oxygen in the V2 site as the model of Ni/ YSZ þ O shown in Fig. 1(b), which is in agreement with the Ni/ YSZ þ O model used in Shishkin and Ziegler's works [27,32]. The charge on the Ni part in Ni/YSZ þ O decreases by 1.04 e as compared with that in the Ni/YSZ based on the Bader charge [43] analysis.…”
Section: Model and Computation Methodsmentioning
confidence: 65%
“…The O 2À ions supplied to the intrinsic vacancy of YSZ originate from the electrochemical reaction of O 2 at an electrode, which depends on the actual SOFC fuel gas operation and polarization conditions in the anode polarization measurement [24e26]. It is found that the favored hydrogen oxidation reaction process on Ni/YSZ is water formation on an O atom at the interface and this is also the most facile hydrogen oxidation reaction process on Ni/(YSZ þ O) [27].…”
Section: Introductionmentioning
confidence: 99%